Trigo-no-metry

If

\(cos \alpha + cos \beta +cos \gamma = sin \alpha + sin \beta +sin \gamma = 0 \)

Then Prove that

cos2α+cos2β+cos2γ=sin2α+sin2β+sin2γ=0cos2 \alpha + cos2 \beta +cos2 \gamma = sin2 \alpha + sin2 \beta +sin2 \gamma = 0

#Algebra #Trigonometry #Proofs

Note by Sudipta Biswas
7 years ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Hi there! Besides complex numbers and/or vectors, I guess a purely trigo proof would be interesting as well (don't worry, it actually isn't at all that messy either...)

So we are given that sinγ=sinαsinβ \sin \gamma = - \sin \alpha - \sin \beta and cosγ=cosαcosβ \cos \gamma = - \cos \alpha - \cos \beta . Then, using the identity sin2γ+cos2γ=1 \sin^2 \gamma + \cos^2 \gamma = 1, and expanding, this results in 2+2sinαsinβ+2cosαcosβ=1 2 + 2 \sin \alpha \sin \beta + 2 \cos \alpha \cos \beta = 1 , and simplifying, we may obtain that cos(αβ)=12 \cos ( \alpha - \beta ) = - \frac{1}{2} , or in other words, the difference between α \alpha and β \beta is 120 degrees. Similarly, since the angles are symmetric, we can say that the difference between β \beta and γ \gamma , as well as the difference between γ \gamma and α \alpha , are 120 degrees as well. In other words, when drawn as the angle from the positive x-axis on cartesian axes, these represent 3 equally spaced angles through the 'cycle' of 360 degrees.

Now, we may then WLOG assume β=α+120 \beta = \alpha + 120 ^ \circ and γ=α120 \gamma = \alpha - 120 ^ \circ .

Hence, sin2α+sin2β+sin2γ \sin 2 \alpha + \sin 2 \beta + \sin 2 \gamma =sin2α+sin(2α+240)+sin(2α240) = \sin 2 \alpha + \sin ( 2 \alpha + 240 ^ \circ ) + \sin ( 2 \alpha - 240 ^ \circ ) =sin2α+2sin2αcos240 = \sin 2 \alpha + 2 \sin 2 \alpha \cos 240 ^ \circ =sin2αsin2α=0 = \sin 2 \alpha - \sin 2 \alpha = 0

Similarly, cos2α+cos2β+cos2γ \cos 2 \alpha + \cos 2 \beta + \cos 2 \gamma =cos2α+cos(2α+240)+cos(2α240) = \cos 2 \alpha + \cos ( 2 \alpha + 240 ^ \circ ) + \cos ( 2 \alpha - 240 ^ \circ ) =cos2α+2cos2αcos240 = \cos 2 \alpha + 2 \cos 2 \alpha \cos 240 ^ \circ =cos2αcos2α=0 = \cos 2 \alpha - \cos 2 \alpha = 0

Jau Tung Chan - 7 years ago

This problem has a familiar ring to it, doesn't it? Something about complex numbers (or maybe vectors). But I don't want to spoil it with the solution.

Michael Mendrin - 7 years ago

Log in to reply

One can also prove that-

cos3α+cos3β+cos3ϒ=3 cos(α+β+ϒ) cos3α + cos3β + cos3ϒ = 3 ~cos(α + β + ϒ)

sin3α+sin3β+sin3ϒ=3 sin(α+β+ϒ) sin3α + sin3β + sin3ϒ = 3 ~sin(α + β + ϒ)

Avineil Jain - 7 years ago

Right, we want to show that if a=b=c=1 |a|=|b|=|c| = 1 and a+b+c=0 a+b+c = 0 then a2+b2+c2=0 a^2+b^2+c^2 = 0 . Pretty straightforward. There is also a nice connection with equilateral triangles...

Patrick Corn - 7 years ago

it can be prooved by usng complex numbers

Dharma Teja - 7 years ago

Ah very nice. I set this question in the practice section. It's an interesting result.

Calvin Lin Staff - 7 years ago

How do you answer this?

Kent Mercado - 7 years ago

why y=a-120

yee cheng - 7 years ago
×

Problem Loading...

Note Loading...

Set Loading...